2013
DOI: 10.1088/0960-1317/23/2/025019
|View full text |Cite
|
Sign up to set email alerts
|

Surface acoustic wave devices on AlN/3C–SiC/Si multilayer structures

Abstract: Surface acoustic wave (SAW) propagation characteristics in a multilayer structure including a piezoelectric aluminum nitride (AlN) thin film and an epitaxial cubic silicon carbide (3C-SiC) layer on a silicon (Si) substrate are investigated by theoretical calculation in this work. Alternating current (ac) reactive magnetron sputtering was used to deposit highly c-axis-oriented AlN thin films, showing the full width at half maximum (FWHM) of the rocking curve of 1.36 • on epitaxial 3C-SiC layers on Si substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…As for the substrate, cubic silicon carbide (3C-SiC) becomes a more attractive candidate since it offers not only a high V (~13,000 m/s) but also a little piezoelectricity when compared to commonly used fast substrates such as diamond and sapphire, etc. Chih-Ming Lin et al [4] theoretically and experimentally demonstrated that the SAW in AlN/3C-SiC/Si multilayer structure with top interdigital transducer (IDT) electrodes exhibits a high V of 5,528 m/s and large K 2 of 0.42% for the fundamental mode while a very small K 2 for the second mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the substrate, cubic silicon carbide (3C-SiC) becomes a more attractive candidate since it offers not only a high V (~13,000 m/s) but also a little piezoelectricity when compared to commonly used fast substrates such as diamond and sapphire, etc. Chih-Ming Lin et al [4] theoretically and experimentally demonstrated that the SAW in AlN/3C-SiC/Si multilayer structure with top interdigital transducer (IDT) electrodes exhibits a high V of 5,528 m/s and large K 2 of 0.42% for the fundamental mode while a very small K 2 for the second mode.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main drawback of such layered structure is that the patterned IDT electrodes harms AlN crystalline growth and causes cracks due to the edge discontinuities of the electrodes [4], [9]. The defects limit both device performance and reliability.…”
Section: Introductionmentioning
confidence: 99%
“…To employ the pyro-and piezoelectric properties in microelectromechanical and electronic devices, c-axis oriented AlN is required [8,9]. The same holds also for acousto-electronic devices [10,11], nonlinear optics and optomechanical devices, [12] as well as phononic crystals [13].…”
Section: Introductionmentioning
confidence: 99%
“…3C-SiC is an attractive candidate substrate given its high velocity and 2 [15,16]. This paper reports a full-wave analysis of YX-PIMNT/3C-SiC substrate conducted via the finite-element method (FEM) with the commercial software package COMSOL Multiphysics.…”
Section: Introductionmentioning
confidence: 99%